Keyakinan Paradoks Kesiapan Menikah pada Anak Pemohon Dispensasi Kawin - Rohmah, Sakinahtul (Pusat Studi Wanita dan Keluarga UGM, 2024)
One-fifth of Indonesia's population engages in child marriage. Child marriages are generally not accompanied by readiness for marriage, which risks negative impacts in the future. This study aims to examine the beliefs of marriage dispensation applicant's child regarding marriage readiness. The approach used was a mixed method embedded design, where qualitative methods are preferred. Data was collected through interviews, observation, and marriage readiness scale. Four children of marriage dispensation applicants at the Malang Regency were research participants. The results showed that participants have a paradoxical beliefs in marriage readiness. Western marriage readiness paradox beliefs were found, such as older age is more ideal, premarital sex strengthens relationships and cohabitation brings benefits. However, these beliefs were not always aligned to participants' behavior. The belief that 20s is the ideal age for marriage also did not align. Although they believed that they were ready for marriage, their readiness was in the moderate category. They acted contrary on marriage readiness preparation due to the belief that premarital sex had no impact on marriage and the subjective norm that premarital sex was normal. This results can be used as a basis for providing education on marriage readiness and risky sexual behavior, especially in adolescents.